The Role of Teacher Scaffolding in Increasing Student Group Discussion Motivation - Teten Nurtaufiqin; Puri Nurani; Suharyanto Soro; Nana Herdiana Abdul Rahman (Civiliza Publishing, Indonesia., 2025)
The effectiveness of learning management in increasing student motivation, especially through the group discussion method, tends to be passive without proper teacher intervention. This study aims to find and analyze the role of teacher scaffolding in increasing the motivation of student group discussions at SMPN 3 Darangdan. The researcher uses a case study approach. The data collection method uses observation, interview, and documentation study methods of school principals, teachers, and grade IX students. The results of the study show that careful planning in mapping students' Zones of Proximal Development (ZPD) as well as the provision of dynamic support (such as hints and encouragement) are significantly able to arouse students' intrinsic motivation and independence. The process of fading or gradually reducing assistance has proven crucial in changing the dynamics of the discussion from passive to active and collaborative. This study concludes that the mastery of scaffolding techniques by teachers is an effective classroom managerial strategy to realize the quality of student-centered learning and in line with the vision of RAMAH at SMPN 3 Darangdan.